Effects of corrective exercises in the guided physical activity on the postural status of the legs and foot arch in preschool children - Stanišić Irena R.; Đorđević Marija M.; Maksimović Sava Z. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2014)
With the aim of investigating the postural status of preschool children and the effectiveness of corrective exercises as part of guided activities in physical education preschool children performed a study on a sample of 60 children (39 girls and 21 boys), aged 6 years, from preschool institution 'Our Joy' in Kruševac in a period of one month. Postural status of the legs were assessed using the methods of Napoleon Volansky. According to them, there are three grades: 0, 1 and 2. The degree of foot arch descending properly estimated using plantogram (interpretation methods - Thomsen's). The results were extracted corresponding to the normal foot, and second degree descending properly. Based on the obtained results it can be concluded that the postural status of the legs and foot in children and determined that the program of corrective exercises in the guided physical activities has a positive effect on correcting these disturbances.